Assessment of seismic station performance in north Chhattisgarh, India: a comprehensive ambient noise analysis - Maitreyi; Chandrani Singh; Arun Singh; Mita Uthaman; Sukanta Sarkar; Gaurav Kumar; Abhisek Dutta; Aamir Salam Siddiqui; Shirish Bose (Geomatics, Natural Hazards & Risk)
A new network of 16 broadband seismic stations is operational in the northern Chhattisgarh region to monitor the seismicity arising in the otherwise seismically quiescent zone. Ambient noise is comprehensively analyzed to evaluate station performance and validate the data quality. Power spectral densities are computed for all stations, comparing ambient noise levels against global limits for data from November 2022 to December 2023. Results indicate that noise levels consistently fall within global noise limits. The study emphasizes the pronounced effect of instrumental tilt on the horizontal components of broadband seismometers. Spatial variation of ambient noise levels across various period bands of the noise spectrum highlights the contribution of diverse noise sources such as anthropogenic activities, surface waves, body waves, and barometric effects. Seasonal variations in short-period, microseism, and long-period bands reveal temporal variation of noise levels. Diurnal variation in the short-period band indicates a prominent effect of cultural noise. Furthermore, the proximity of seismic stations to major mining areas induces high noise levels in the very short-period band during blasting activities compared to non-blasting periods. Our study thus explores the variability of the ambient noise environment while validating the robustness and stability of the seismic installation across the study region.